Synthesis of Essentialism and Reconstructionism: Philosophical Relevance in the Transformation of General Education and Christian Religious Education - Manu, Sendi Marlina; Josefina, Sari; Tateni, Sandro; Pellokila, Ireni Irnawati (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This research aims to formulate a philosophical synthesis between Essentialism and Reconstructionism and its relevance to the transformation of General Education and Christian Religious Education (CRE). On one hand, Essentialism emphasizes the preservation of core values and established cultural heritage. On the other hand, Reconstructionism encourages education as an instrument of social change towards a more just world order. Using a qualitative research method with a literature study approach, the results indicate that the synthesis of these two schools of thought creates an educational model that is